Antioxidant activity of pitcher extracts from three Nepenthes species - Muhammad Aqil Fitri Rosli; Kamalrul Azlan Azizan; Goh, Hoe-Han (Penerbit Universiti Kebangsaan Malaysia, 2018)
Nepenthes, locally known as ‘periuk kera’ in Malaysia, is a fascinating species due to uniqueness in their morphology in having pitcher organ for carnivorous diet. The pitcher plant has been used for cooking traditional delicacies and as traditional remedies to treat illness. Hence, this species might possess beneficial health properties. This study aimed to compare the antioxidant activity of the pitcher extracts from Nepenthes ampullaria, Nepenthes rafflesiana and their hybrid, Nepenthes × hookeriana. The samples were extracted using methanol:chloroform:water (3:1:1) via sonication assisted extraction and the extracts were subjected to three different antioxidant assays, namely 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing power (FRAP) and total phenolic content (TPC). Extract from N. ampullaria exhibited the strongest radical scavenging activity (0.148 ± 0.04 mg/mL) with the highest ferric reducing power (0.009 ± 0.003 mg GA/mg dry weight) among the three species, whereas that of N. rafflesiana possessed the highest phenolic content (0.057 ± 0.017 mg GA/mg dry weight). However, the antioxidant capacities of the pitcher extracts were not significantly different (p>0.05) between the three species and were much lower than the gallic acid as a standard reference.